Polymer micro-lenses as an long-coupling-distance interfacing layer in low-cost optical coupling solution between optical fibers and photonic integrated waveguide circuits - Kaźmierczak, Andrzej; Słowikowski, Mateusz; Pavłov, Krystian; Filipiak, Maciej; Piramidowicz, Ryszard (Photonics Letters of Poland, 2019)
We present a low-cost scheme for non-permanent optical signal coupling for prospective application in single use photonic integrated chips. The proposed scheme exploits the use of polymer kinoform microlenses. The feasibility of the proposed solution is demonstrated by the experimental investigation of the optical signal coupling from single mode optical fiber (SMF) to the test structure of SixNy integrated waveguide. Full Text: PDF References M. Smit et al., "An introduction to InP-based generic integration technology," Semiconductor Science and Technology, 29 (8), 083001, 2014 CrossRef R. Baets et al., "Silicon Photonics: silicon nitride versus silicon-on-insulator," in Optical Fiber Communication Conference, OSA Technical Digest (online) (Optical Society of America, 2016), paper Th3J.1. CrossRef K. Shiraishi et al., "A silicon-based spot-size converter between single-mode fibers and Si-wire waveguides using cascaded tapers," Appl. Phys. Lett. 91, 141120 (2007) CrossRef Y. Sobu et al., "GaInAsP/InP waveguide dual core spot size converter for optical fiber,"IEEE Photonic Society 24th Annual Meeting, 469-470, (2011). CrossRef F. Van Laere et al., "Compact and Highly Efficient Grating Couplers Between Optical Fiber and Nanophotonic Waveguides," Journal of Lightwave Technology, vol. 25, no. 1, pp. 151-156, Jan. 2007. CrossRef A. Kaźmierczak et al., "Light coupling and distribution or Si3N4/SiO2 integrated multichannel single mode sensing system," Opt. Eng. 48, 2009, pp. 014401 CrossRef M. Rossi et al., "Arrays of anamorphic phase-matched Fresnel elements for diode-to-fiber coupling," Appl. Opt. 34, 2483-2488 (1995) CrossRef M. Prasciolu et al, "Fabrication of Diffractive Optical Elements On-Fiber for Photonic Applications by Nanolitography," Japanese Journal of Applied Physics, Volume 42, (2003) CrossRef F.Schiappelli et al., "Efficient fiber-to-waveguide coupling by a lens on the end of the optical fiber fabricated by focused ion beam milling" Microelectronic Engineering Volumes 73-74, pp.397-404 (2004) CrossRef